Segmentasi permintaan pasar kopi dan komoditas terkait di Kabupaten Karanganyar: Tinjauan elastisitas harga, pendapatan, sosial, dan demografis - M. Wahyuddin (Universitas Islam Indonesia, 2000)
The role of agricultural product for economic development in Indonesia is very important. One of the products is coffee where Indonesia is the biggest producer in South East Asian. This paper analysis the demand for coffee in Karanganyar regency by using the price and income elasticity as well as non-economic variables.